2014
DOI: 10.1007/978-3-662-43492-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Manipulation of cIL-10 Signaling Pathways: Opportunities for Vaccine Development?

Abstract: Interleukin-10 (IL-10) is a tightly regulated, pleiotropic cytokine that has profound effects on all facets of the immune system, eliciting cell-type-specific responses within cells expressing the IL-10 receptor (IL-10R). It is considered a master immune regulator, and imbalances in IL-10 expression, resulting from either inherent or infectious etiologies, have far reaching clinical ramifications. Regarding infectious diseases, there has been accumulating recognition that many pathogens, particularly those tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 166 publications
(162 reference statements)
0
17
0
Order By: Relevance
“…Exploitation of cellular interleukin-10 (cIL-10) or IL-10 receptor (IL-10R) signaling is a common theme in the natural histories of diverse pathogenic and nonpathogenic microbes that establish lifelong persistence, including viruses, pathogenic and commensal bacteria, protozoa, helminths, and fungi (4)(5)(6)(7). This unifying linkage via cIL-10 suggests the potential for development of novel interventions to prevent and/or disrupt persistent infections.…”
mentioning
confidence: 99%
“…Exploitation of cellular interleukin-10 (cIL-10) or IL-10 receptor (IL-10R) signaling is a common theme in the natural histories of diverse pathogenic and nonpathogenic microbes that establish lifelong persistence, including viruses, pathogenic and commensal bacteria, protozoa, helminths, and fungi (4)(5)(6)(7). This unifying linkage via cIL-10 suggests the potential for development of novel interventions to prevent and/or disrupt persistent infections.…”
mentioning
confidence: 99%
“…Studies of MCMV-infected mice revealed that there is a marked increase in the number of CD4 ϩ cells expressing cIL-10 in tissue sites of persistence (salivary glands) but not in tissues where MCMV establishes a latent infection (e.g., spleen) (7). While MCMV does not encode an ortholog of cIL-10, the results of this study imply that MCMV, like many viral and nonviral pathogens (3), has co-opted the cIL-10/IL-10R1 signaling cascade to enable persistence in an immune host.…”
mentioning
confidence: 58%
“…Human cytomegalovirus (HCMV) is a ubiquitous persistent pathogen with worldwide seroprevalence rates in adults that range from ϳ50 to 100%, and there is accumulating evidence that persistence is mediated through viral modulation of host immunity, including manipulation of the IL-10R pathway (3,(8)(9)(10). HCMV is generally considered a virus with low pathogenic potential in immunocompetent hosts, consistent with the interpretation that host immune responses to HCMV infection are protective against HCMV sequelae.…”
mentioning
confidence: 89%
See 2 more Smart Citations